A centenary for bacterial spot of tomato and pepper. (2nd September 2021) - Osdaghi, Ebrahim; Jones, Jeffrey B.; Sharma, Anuj; Goss, Erica M.; Abrahamian, Peter; Newberry, Eric A.; Potnis, Neha; Carvalho, Renato; Choudhary, Manoj; Paret, Mathews L.; Timilsina, Sujan; Vallad, Gary E.
Abstract: Disease symptoms: Symptoms include water‐soaked areas surrounded by chlorosis turning into necrotic spots on all aerial parts of plants. On tomato fruits, small, water‐soaked, or slightly raised pale‐green spots with greenish‐white halos are formed, ultimately becoming dark brown and slightly sunken with a scabby or wart‐like surface. Host range: Main and economically important hosts include different types of tomatoes and peppers. Alternative solanaceous and nonsolanaceous hosts include Datura spp., Hyoscyamus spp., Lycium spp., Nicotiana rustica, Physalis spp., Solanum spp., Amaranthus lividus, Emilia fosbergii, Euphorbia heterophylla, Nicandra physaloides, Physalis pubescens, Sida glomerata, and Solanum americanum . Taxonomic status of the pathogen: Domain, Bacteria; phylum, Proteobacteria ; class, Gammaproteobacteria ; order, Xanthomonadales ; family, Xanthomonadaceae ; genus, Xanthomonas ; species, X . euvesicatoria, X . hortorum, X . vesicatoria . Synonyms (nonpreferred scientific names): Bacterium exitiosum, Bacterium vesicatorium, Phytomonas exitiosa, Phytomonas vesicatoria, Pseudomonas exitiosa, Pseudomonas gardneri, Pseudomonas vesicatoria, Xanthomonas axonopodis pv. vesicatoria, Xanthomonas campestris pv. vesicatoria, Xanthomonas cynarae pv. gardneri, Xanthomonas gardneri, Xanthomonas perforans . Microbiological properties: Colonies are gram‐negative, oxidase‐negative, and catalase‐positive and have oxidative metabolism. Pale‐yellow domed circular colonies of 1–2 mm in diameter grow on general culture media. Distribution: The bacteria are widespread in Africa, Brazil, Canada and the USA, Australia, eastern Europe, and south‐east Asia. Occurrence in western Europe is restricted. Phytosanitary categorization: A2 no. 157, EU Annex designation II/A2. EPPO codes: XANTEU, XANTGA, XANTPF, XANTVE. Abstract : In this review we provide a historical perspective as well as an updated overview on the aetiology, epidemiology, and management strategies of bacterial spot of tomato and pepper.